The 300 most cited articles published in periodontology - Faggion Junior, Clóvis Mariano; Trescher, Anna-Lena; Listl, Stefan (Clinical oral investigations, 2017)
ObjectivesIt is important to evaluate the characteristics of the most cited articles in any specialty. The number of citations may be a proxy for clinical and research activity. The objectives of the present methodological study were (1) to report the characteristics of the 300 most cited articles in periodontology and (2) to explore the association of these characteristics with the number of citations.MethodsWe searched in the Web of Science database for the 300 most cited articles published in periodontology on June 15, 2015. We described characteristics of the articles such as type of study, type of scientific journal, topic reported, year of publication, affiliation of the first author of the article, and impact factor. Linear regression analysis was used to investigate associations of these variables with the number of citations.ResultsThe search retrieved approximately 155,356 publications; out of the studies that met the eligibility criteria, the 300 most cited were included for analysis. Comprising more than 50 % of the included articles, basic biology and the detection of bacteria were the most prevalent topics. Narrative reviews were the most frequent type of article (27 % of the sample). Regression analysis demonstrated that some characteristics, for example “narrative reviews,” are more prone to be cited than others.ConclusionWe conclude that scientific evolution in periodontology has been based more on narrative reviews than on reproducible systematic reviews.Clinical relevanceFuture research is encouraged to elucidate the extent to which scientific progress is improved through systematic compared with narrative reviews.